Experienced Teachers’ Thoughts and the Teaching of Oral Communication - Koh, Soo Ling (INTI Publishing House Sdn. Bhd., 2006)
A teacher’s thoughts are very much influenced by his knowledge systems and beliefs. These two components will certainly have an impact on the way he performs in the classroom. These will influence the conception of the teaching tasks, the teachers’ teaching strategies and classroom decisions. These two components need to be studied in greater detail, identifying how they interact with each other and influence teachers’ classroom practice. The researcher’s purpose in this current investigation on oral communication is to construct a context to enable us to see the influence of experienced teachers’ thought processes on their classroom practices. Predominant categories are thoughts pertaining to students’ behavior, classroom management, students’ participation in classroom tasks and self-improvement. Teachers’ thoughts, influenced by their knowledge systems and beliefs need to be studied in greater detail. How knowledge systems and beliefs interact with each other and the effects teachers beliefs have on student outcomes are worthwhile areas of research. A comparison between novice teachers’ thoughts and experienced teachers’ thoughts can also shed more light into what governs good classroom practice.